Pemetaan Potensi Desa Dalam Rangka Menuju Desa Wisata Desa Sidoharjo Kecamatan Samigaluh Kulonprogo Yogyakarta - Dina Natasari; Rizky Wulandari; Sumirah Sumirah; Nabella Duta Nusa (Jurnal Pengabdian dan Pengembangan Masyarakat, 2021)
Sidoharjo village has natural resources that can be used to increase the community welfare. The village government has formed BUMDes in an effort to improve the welfare of the community. However, the BUMDes has not yet played an optimal role in community empowerment. There is no synergy between the activities of the village government, business actors, and BUMDes so that the management of resources has not had an impact on improving the welfare of village communities. The solution offered in Community Service activities is identification and mapping the potential natural resources in Sidoharjo. The result of this activity can be used as source data to plan new business unit in BUMDes. Thus it is hoped that BUMDes can emerge as one of the new economic forces based on local potential in Sidoharjo Village. Mapping the natural resource of the village begins with a number of discussions with village officials, tourism awareness groups, and businesses to get preliminary data on existing problems. Then the survey is carried out in several stages to get the latest data on the potential of existing resources. The results of the activities in the form of village potential manuscripts and also tourism potential videos are expected to be used as preliminary data for planning the development of new business units under the management of BUMDes so that the utilization of natural resource potential is more optimal. It is hoped that this will drive the economy in Sidoharjo Village, which has an impact on improving community welfare.